Colonnade of the Principal du Petit Palais - N.D.:::::::::
Petit Palais, Paris, France, 1900. Colonnade of the Principal du Petit Palais. Brooklyn Museum Archives, Goodyear Archival Collection (S03_06_01_015 image 2129)